Students' Perceptions of Career Guidance Services Towards the Selection of College Majors - Panjaitan, Rizki Ajhari; Daulay, Nurussakinah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study was to determine the Perception of Class XII Students of SMA Negeri 1 Kualuh Hilir, Labuhanbatu Utara Regency, towards Career Guidance Services During the Selection Period of College Majors. This type of research is descriptive qualitative research. The data collection techniques used in this research are interviews, observation, and documentation. While data analysis uses data reduction, data presentation, and conclusion drawing. From this study, it can be concluded that students' perceptions of career guidance in choosing majors during college already have an understanding. This is evidenced by the attitude that students bring up when participating in career guidance activities. Students determine their choice of majors during college for full consideration and adjust to their potential. Students also have information on career orientation after they are later able to complete their studies in college.